THEME: CULTURAL COMPETENCE AND INTERCULTURAL COMMUNICATION - Norqobilov Boburjon; Safarova Dildora; Salokhiddinov Dilshodbek (Ustozlar uchun, 2025)
Cultural competence and intercultural communication are essential skills in our globalized world, allowing individuals to interact effectively across diverse cultures. Understanding different values, traditions, and communication styles fosters mutual respect and minimizes misunderstandings. This article explores the significance of cultural competence, its components, and strategies for improving intercultural communication. It also highlights challenges such as ethnocentrism and cultural bias. Mastering these skills is crucial in education, business, and social interactions, promoting inclusivity and cooperation in diverse environments.